Characteristics and performance of professionals of the Expanded Family Health and Basic Healthcare Centers - Vendruscolo, Carine; Metelski, Fernanda Karla; Maffissoni, André Lucas; Tesser, Charles Dalcanale; Trindade, Letícia de Lima (Revista da Escola de Enfermagem da USP, 2020)
OBJECTIVE To analyze the characteristics and performance of the teams of the Expanded Family Health and Basic Healthcare Centers (Nasf-AB) of Santa Catarina state. METHOD A multicenter study implementing mixed methods, a sample of 149 municipalities (50.5% of the state) and 359 professionals through applying a survey and collective interviews with five teams of 43 professionals. Quantitative data were analyzed using descriptive statistics, and qualitative data were subjected to thematic analysis. RESULTS There were 11 professions integrated to the Centers with a predominance of psychologists (27%), physiotherapists (18%) and nutritionists (18%). The professionals were mostly women (88%) aged between 30 and 39 years (50.4%), with their performance involving shared care, collective activities of their professional core, group activities and individual care to users. Professionals participate in the intermediation, regulation or evaluation of referrals from Primary Care to other points of the Network. The interviews revealed a set of actions of technical care and technical-pedagogical support and specialized actions. CONCLUSION Despite operational difficulties, the Expanded Family Healthcare Centers have been supporting Family Healthcare teams, strengthening Primary Care.